Clinical significance of SARS‐CoV‐2‐specific IgG detection with a rapid antibody kit for COVID‐19 patients. Issue 1 (10th September 2020) - Chong, Yong; Ikematsu, Hideyuki; Tani, Naoki; Arimizu, Yoko; Watanabe, Haruka; Fukamachi, Yukako; Yonekawa, Akiko; Iwasaka, Sho; Nishida, Ruriko; Eriguchi, Yoshihiro; Miyake, Noriko; Shimoda, Shinji; et al.
Abstract: Background: The longitudinal observation of the detection of antibody responses to SARS‐CoV‐2 using antibody kits during the clinical course of COVID‐19 is not yet fully investigated. Objectives: To understand the significance of the detection of anti‐SARS‐CoV‐2 antibodies, particularly IgG, using a rapid antibody kit, during the clinical course of COVID‐19 patients with different severities. Methods: Sixty‐three serum samples from 18 patients (5 asymptomatic and 13 symptomatic patients) were retrospectively examined using a commercial SARS‐CoV‐2 IgM/IgG antibody kit. PCR positivity of patient samples was also examined as a marker of current SARS‐CoV‐2 infection. Results: IgG antibodies were detected in all cases in this study. The IgG detection rates reached 100.0% in samples collected on day 13 or later. IgG seropositivity after an initial negative status was observed in 13 patients (3/5 asymptomatic and 10/13 symptomatic cases). Interestingly, the persistence of both PCR and IgG positivity was detected in seven cases, of which three were asymptomatic. The longest overlap duration of the PCR and IgG positivity was 17 days in asymptomatic status. Conclusions: SARS‐CoV‐2‐specific IgG production can be detected in all infected individuals, using a rapid antibody kit, irrespective of clinical status. However, these findings suggest that, in some infected individuals, particularly those with asymptomatic status, the presence of virus‐specific IgG antibodies does not imply prompt viral clearance.